Interactions between climate and COVID-19. Issue 10 (October 2022) - Ford, James D; Zavaleta-Cortijo, Carol; Ainembabazi, Triphini; Anza-Ramirez, Cecilia; Arotoma-Rojas, Ingrid; Bezerra, Joana; Chicmana-Zapata, Victoria; Galappaththi, Eranga K; Hangula, Martha; Kazaana, Christopher; Lwasa, Shuaib; Namanya, Didacus; et al.
Summary: In this Personal View, we explain the ways that climatic risks affect the transmission, perception, response, and lived experience of COVID-19. First, temperature, wind, and humidity influence the transmission of COVID-19 in ways not fully understood, although non-climatic factors appear more important than climatic factors in explaining disease transmission. Second, climatic extremes coinciding with COVID-19 have affected disease exposure, increased susceptibility of people to COVID-19, compromised emergency responses, and reduced health system resilience to multiple stresses. Third, long-term climate change and prepandemic vulnerabilities have increased COVID-19 risk for some populations (eg, marginalised communities). The ways climate and COVID-19 interact vary considerably between and within populations and regions, and are affected by dynamic and complex interactions with underlying socioeconomic, political, demographic, and cultural conditions. These conditions can lead to vulnerability, resilience, transformation, or collapse of health systems, communities, and livelihoods throughout varying timescales. It is important that COVID-19 response and recovery measures consider climatic risks, particularly in locations that are susceptible to climate extremes, through integrated planning that includes public health, disaster preparedness, emergency management, sustainable development, and humanitarian response.